LICIACube - The Light Italian Cubesat for Imaging of Asteroids In support of the NASA DART mission towards asteroid (65803) Didymos. (May 2021) - Dotto, E.; Della Corte, V.; Amoroso, M.; Bertini, I.; Brucato, J.R.; Capannolo, A.; Cotugno, B.; Cremonese, G.; Di Tana, V.; Gai, I.; Ieva, S.; Impresario, G.; et al.
Abstract: "LICIACube – the Light Italian Cubesat for Imaging of Asteroids" is managed by the Italian Space Agency (ASI) and will be part of the NASA DART mission, with the aim of i) documenting the DART impact's effects on the secondary member of the (65803) Didymos binary asteroid system, ii) characterizing the shape of the target, and iii) performing dedicated scientific investigations on it. DART probe will be launched at the end of 2021 and LICIACube will be hosted as piggyback during the interplanetary cruise, then released 10 days before the impact, and autonomously guided along its fly-by trajectory. The LICIACube payload is composed by LEIA, a narrow FoV camera, and LUKE, a wide FoV imager with an RGB Bayer pattern filter, that will collect and transmit to Earth several unique images of the effects of the DART impact on the asteroid, such as the formation and the development of the plume potentially determined by the impact. LICIACube will be the first deep space mission developed and autonomously managed by an Italian team: the design, integration and test of the CubeSat have been assigned by ASI to the aerospace company Argotec, while the LICIACube Ground Segment has a complex architecture based on the Argotec Mission Control Center, antennas of the NASA Deep Space Network and data archiving and processing, managed at the ASI Space Science Data Center. The LICIACube team includes a wide Italian scientific community, involved in the definition of all the aspects of the mission: trajectory design; mission definition (and real-time orbit determination during operations); impact, plume and imaging simulation and modelling, in preparation of a suitable framework for the analysis and interpretation of in-situ data. The major technological mission challenge, i.e. the autonomous targeting and imaging of such a small body during a fast fly-by, to be accomplished with the limited resources of a CubeSat, is affordable thanks to a strong synergy of all the mentioned teams in support of the engineering tasks. Highlights: - LICIACube is the first purely Italian spacecraft operating in deep space. -LICIACube is managed by the Italian Space Agency and will be part of the NASA DART mission. -It will analyze the output of the first kinetic impact test at a realistic scale. -The payload is composed by LEIA, a narrow FoV camera, and LUKE, a wide FoV imager with an RGB Bayer pattern filter. -Aims: documenting the DART impact on Dimorphos; characterizing the target shape; performing scientific investigations.